2007
DOI: 10.1111/j.1365-2265.2007.02835.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal DXA bone mineral density but frail cortical bone in Turner's syndrome

Abstract: Bone fragility in Turner's syndrome is reflected by low SOS but not by DXA BMD. Low QUS, which assesses the cortical bone only, supports a defect in cortical bone in Turner's syndrome. Lack of SOS correlation with age, height and hormonal therapy in Turner's syndrome suggests a primary bone defect, rather than enhanced resorption of endocrine origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 45 publications
2
26
0
1
Order By: Relevance
“…9 Moreover, they found no differences in the total vBMD Z-score or the trabecular vBMD Z-score at the distal radius. Using ultrasound methods, comparable results were obtained by Zuckerman-Levin et al and Vierucci et al 24,26 As in our study, they found reduced phalangeal Ad-SoS, and radial and tibial SoS in girls and women with TS. As with pQCT data, abnormal QUS results may imply structural abnormalities in cortical bone in TS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…9 Moreover, they found no differences in the total vBMD Z-score or the trabecular vBMD Z-score at the distal radius. Using ultrasound methods, comparable results were obtained by Zuckerman-Levin et al and Vierucci et al 24,26 As in our study, they found reduced phalangeal Ad-SoS, and radial and tibial SoS in girls and women with TS. As with pQCT data, abnormal QUS results may imply structural abnormalities in cortical bone in TS.…”
Section: Discussionsupporting
confidence: 92%
“…20,21 However, reduced cortical BMD in young TS patients is not proven to lead to increased fractures. [22][23][24] We assessed the skeletal status of a group of young females with TS at 2 different skeletal sites using 2 different densitometric techniques. Phalangeal QUS measurements have shown an ability to reveal changes due to skeletal disorders and seem to be less influenced by bone size.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, vBMD was similar or higher at the spine and comparable at the hip in TS, only being lower in young TS, emphasizing that reduced bone size explains the reduced aBMD. Previously, the shaft of the radius, predominately consisting of cortical bone, was found selectively reduced in adult TS, independently of the effects of estrogen treatment [18,24,25], while sites predominately consisting of trabecular bone are highly estrogen-dependent [26] and higher doses may even increase the bone mass [6,27]. In extension of this, normal cortical bone has been seen in pre-pubertal TS girls [25,28] to suggest that lack of estrogen may too be involved in the pathogenesis of cortical bone deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, BMD is regarded as a poor independent predictor of osteoporosis and fracture risk in TS [18,19]. Therefore, we undertook the present cross-sectional study to evaluate aBMD and vBMD by DXA, and their association to bone markers and hormones related to bone metabolism in children and adolescents with TS.…”
Section: Introductionmentioning
confidence: 99%
“…Bone size-independent methods, such as QCT or volumetric transformation of DEXA data, should be used in individuals shorter than 150 cm. Achieving optimal bone density is of critical importance for fracture prevention in TS, and should be pursued by timely introduction of hormone replacement therapy, adequate dose of estrogens during young adult life, optimal calcium and vitamin D intake, and regular physical exercise (57).…”
Section: Bone Mass Gain and Prevention Of Fractures In Turner Syndromementioning
confidence: 99%